2009
DOI: 10.2215/cjn.03860808
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function in Older Candidates for Renal Transplantation

Abstract: Background and objectives: Although physical function is a major determinant of health outcomes and quality of life in older adults, standard tools for its assessment have not been routinely applied to the fastest growing segment of the kidney transplant candidate population, which is at high risk of comorbidity and disability-people over age 60. The objective of this study was to describe the baseline physical function in older adults with renal failure referred for transplantation and compare them with older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 45 publications
4
58
1
Order By: Relevance
“…With regard to individual components of SPPB, this association persisted for muscle Studies have shown individuals with end-stage renal disease have significantly lower physical functioning compared to the general population, 42 as well as in comparison to those with other common chronic diseases, such as diastolic heart failure, chronic obstructive pulmonary disease, or at high risk for cardiovascular disease. 31 Our data confirmed that patients with reduced renal function (eGFR levels = 30-45.9 mL/min per 1.73 m 2 ) were more likely to have poorer total physical performance and had on average almost 1 SPPB point less than patients with levels of eGFR ‡ 60 mL/min per 1.73 m 2 . These findings seem of interest when considering that physical functioning strongly predicts morbidity and mortality in community-dwelling older adults.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With regard to individual components of SPPB, this association persisted for muscle Studies have shown individuals with end-stage renal disease have significantly lower physical functioning compared to the general population, 42 as well as in comparison to those with other common chronic diseases, such as diastolic heart failure, chronic obstructive pulmonary disease, or at high risk for cardiovascular disease. 31 Our data confirmed that patients with reduced renal function (eGFR levels = 30-45.9 mL/min per 1.73 m 2 ) were more likely to have poorer total physical performance and had on average almost 1 SPPB point less than patients with levels of eGFR ‡ 60 mL/min per 1.73 m 2 . These findings seem of interest when considering that physical functioning strongly predicts morbidity and mortality in community-dwelling older adults.…”
Section: Discussionsupporting
confidence: 80%
“…24 Recently, SPPB has been shown to predict incident disability and death in older patients following discharge from acute care hospitals. 20,30 In CKD, SPPB has been used to compare physical performance of CKD patients and patients with other chronic diseases, 31 and it has been considered as primary outcome measure in a recent randomized pilot trial of resistance training during maintenance dialysis. 32 However, the relationship between renal function and SPPB performance has never been formally assessed in older hospitalized adults.…”
Section: Introductionmentioning
confidence: 99%
“…Portions of this work were presented at the American Society of Nephrology Renal Week in Denver, CO (November [16][17][18][19][20][21]2010 …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…These data suggest that treating acidosis might improve muscle strength and function by reducing muscle breakdown and preserving, or even increasing, muscle mass, which could positively affect the poor physical function and exercise capacity of patients with CKD (16,17). Although acidosis seems a prudent target for intervention, the effect of its treatment on functional outcomes has not been addressed previously.…”
Section: Introductionmentioning
confidence: 98%
“…Lower self-reported physical functioning is associated with higher mortality and higher rates of hospitalization (9)(10)(11)(12). Prior studies in CKD cohorts have reported lower levels of physical functioning, particularly among whites, older persons, and persons with diabetes and peripheral arterial disease (3,11,13,14).…”
Section: Introductionmentioning
confidence: 99%